Public mental healthcare and economic vulnerability in Sri Lanka - Nadia Augustyniak (SSM - Mental Health)
Scholars and practitioners in Sri Lanka's mental health and psychosocial field have long highlighted the complex cultural, social and political dynamics of providing care to communities impacted by war and natural disaster and facing a fraught post-war context. One critical contribution of this work has been to offer a practice-based corrective to psychological conceptions of wellbeing that obscure its relational, economic, and political dimensions. In this article, I consider the importance of this insight in light of the 2022 debt crisis in Sri Lanka and against the backdrop of global mental health discourses that continue to elide the question of structural determinants of distress. Based on ethnographic research conducted between 2018 and 2020, I highlight the practice of government counselors and other mental health professionals in one district of Sri Lanka's Central Province. Their experiences suggest that despite expanded access to mental health services over the last 20 years, care is undermined by the structural realities of widespread economic precarity and inadequate social protections. This problematizes the global discourse of access to mental health care—which implies but often does not truly account for the social and economic bases of wellbeing—and underscores the fact that expansion of mental health services should go hand in hand with the expansion of social protections and economic support.